Cholesterol Level In Injectable Contraception Acceptors - Esty Puji Rahayu; Annif Munjidah (Universitas STRADA Indonesia, 2021)
This study used a cross sectional study. The population was DMPA and Cyclofem injection family planning acceptors, while the sampling technique used purposive sampling technique. Based on the results of data analysis with the Paired T test, it was found that DMPA acceptors had higher cholesterol levels (mean = -1.822; SD = 45.34; p <0.005) than cyclofem acceptors (mean = 1.722; SD = 35.51; P <0.005). Contraceptive injections cause changes in fat metabolism through changes in HDL and LDL levels. HDL is antiatherogenic, on the other hand, high levels of LDL and triglycerides cause cardiovascular disease in the periphery and coronary arteries which cause cardiovascular disease. Long-term use of hormonal contraceptives causes an increase in LDL, whereas HDL varies